Amnesty for Kurdish Genocide Perpetrators in the Perspective National and International Law - Ahmed, Awara Hussein (Universitas Islam Negeri Raden Intan Lampung, 2024)
The concept of amnesty has long been a subject of debate, especially when it concerns those responsible for heinous crimes such as genocide. This study aims to analyze the legal implications of the 1991 general amnesty issued by the Kurdistan Council, focusing on its impact on victims' rights and transitional justice from both national and international legal perspectives. Employing a legal analysis method, the research examines laws, court decisions, conventions, and relevant statutes, as well as academic studies and legal documents. The findings reveal that, based on legal principles at both domestic and international levels, perpetrators of international crimes in general, and genocide in particular, cannot escape legal accountability. Amnesty is inconsistent with the principles of equality and the protection of all individuals before the law. However, if amnesty must be chosen as a last resort and is entirely unavoidable, this legal flaw can be rectified by prosecuting the perpetrators in court.